BIELOMATIC MACHINE PRODUCTIVITY ANALYSIS USING OVERALL EQUIPMENT EFFECTIVENESS (OEE) METHOD: CASE STUDY - ari andriyas puji (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2022)
Productivity is an activity in producing an item or product using the most effective and efficient way possible. To increase the productivity of machines/equipment, it is necessary to apply TPM. Section CV 6 has applied the TPM method, but it doesn't work consistently so there are still a lot of loss time. As a result of the loss time, the resulting production is not in accordance with the company's target. So the purpose of this research is to measure the productivity level of a bielomatic machine by using the Overall Equipment Effectiveness (OEE) method and to minimize the Six Big Losses which are the cause of the decline in engine performance. Based on the results of the implementation of the method and discussion, the results of the calculation of the OEE value from 62.76% - 80.03%, it can be concluded that the bielomatic machine still has an OEE value below the standard 85%. From the calculation of the six big losses, several factors were found that caused the low productivity of bielomatic machines, namely the setup and adjustment, Equipment Failure, and Reduced Speed ​​sections. This study also provides input for improvements in the setup and adjustment, Equipment Failure, and Reduced Speed ​​sections after parsing existing problems using Fishbone diagrams.